Ketahanan Sosial Dan Pengaruhnya Terhadap Penyalahgunaan Narkoba Pada Remaja: Perspektif Teori Kontrol Sosial Travis Hirschi - Puguh Sunoto, Suyud; Kurniawan Aziz, Wawan; Dhesthoni, Dhesthoni (UI Scholars Hub, 2023)
Abstract This article explores the relationship between social resilience and drug abuse, utilizing Travis Hirschi's Social Control Theory as a framework. Focusing on social bonds, engagement in positive activities, belief in social norms, and commitment to legitimate goals, the article demonstrates that strong social investment can reduce the tendency of drug abuse among adolescents. Through empirical data and case studies, this article highlights the importance of strengthening social resilience in designing effective prevention strategies concerning drug abuse among adolescents.